GPU-accelerated rendering of vector strokes with piecewise quadratic approximation - Xuhai Chen; Guangze Zhang; Wanyi Wang; Juan Cao; Zhonggui Chen (Graphical Models)
Vector graphics are widely used in areas such as logo design and digital painting, including both stroked and filled paths as primitives. GPU-based rendering for filled paths already has well-established solutions. Due to the complexity of stroked paths, existing methods often render them by approximating strokes with filled shapes. However, the performance of existing methods still leaves room for improvement. This paper designs a GPU-accelerated rendering algorithm along with a curvature-guided parallel adaptive subdivision method to accurately and efficiently render stroke areas. Additionally, we propose an efficient Newton iteration-based method for arc-length parameterization of quadratic curves, along with an error estimation technique. This enables a parallel rendering approach for dashed stroke styles and arc-length guided texture filling. Experimental results show that our method achieves average speedups of 3.4× for rendering quadratic stroked paths and 2.5× for rendering quadratic dashed strokes, compared to the best existing approaches.